Significado em práticas matemáticas não escolares: estudo com alunos do ensino fundamental - Costa, Daniela Netto Scatolin (2014)
This research has the purpose to analyze the influence of situations in order to deal with mathematics in different social practices. As a specific goal, it investigates the meanings in various school and non-school mathematical practices. Among these purposes there is an analysis about the switch of meanings between one and another practice. The development of this work is based on a review of studies about the exploitation of Mathematics on the day to day problems and in other areas of knowledge that could contribute to the learning of mathematics as a school subject. Considering the idea of mathematics as a social practice, the theoretical framework of the present research has centered on the design of means of structuring and situated learning by Jean Lave. The research follows a naturalistic perspective with ethnographicins piration and uses as a methodological resource the participant observation with a group of elementary school students. The data collected were recorded by the researcher in field activities, through interviews, diaries and field recordings. The activities observed occur inside and outside the school. For the analysis it is considered the resource association between the object and the theoretical framework consisting drawn from Lave s studies. Concerning the results obtained, it is possible to realize the strength of the situation and sometimes, how crucial it is in order to practice math. It stands out especially the prevalence of different meanings in different practices. The present study also promotes questions about the proposal to take the students everyday situations to inside the classroom and therefore, it intermediates my work as a mathematics teacher at elementary schools.